2004
DOI: 10.1161/01.cir.0000145118.55201.15
|View full text |Cite
|
Sign up to set email alerts
|

There Is No Evidence for an Increase in Acute Coronary Syndromes After Short-Term Abrupt Discontinuation of Statins in Stable Cardiac Patients

Abstract: Background-For a variety of reasons, many patients abruptly discontinue statin therapy. The present analysis was conducted to determine whether the risk of cardiovascular outcomes increases after withdrawal of statin therapy in a stable cardiac population. Methods and Results-In the Treating to New Target (TNT) study, 2 doses of atorvastatin (10 and 80 mg once daily) are being used in a double-blind parallel-group design. Of the 18 468 patients screened for study participation, 16 619 entered a dietary lead-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(43 citation statements)
references
References 30 publications
2
39
0
2
Order By: Relevance
“…In addition, we confirmed that statin interruption did not cause any Serious Adverse Event as expected from an earlier report [24], and no cardiovascular disease was observed during the 12-week study period. Our results confirm the observations from clinical trials comparing newer drugs with standard treatments including boosted PI.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, we confirmed that statin interruption did not cause any Serious Adverse Event as expected from an earlier report [24], and no cardiovascular disease was observed during the 12-week study period. Our results confirm the observations from clinical trials comparing newer drugs with standard treatments including boosted PI.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, the National Registry of Myocardial Infarction showed that withdrawal of statin therapy in the first 24 h of hospitalization for non-ST segment elevation myocardial infarction is associated with worse hospital outcome (Spencer et al, 2004b). In contrast, the Treating to New Target (TNT) Study Group found no evidence for an increase in acute coronary syndromes after short-term abrupt discontinuation of statins in stable cardiac patients (McGowan et al, 2004). Presently, there are no data available regarding statin withdrawal in stroke patients.…”
Section: Clinical Evidencementioning
confidence: 99%
“…been described the existence of the rebound effect after transient suspension of statin therapy [8], it is also reported that short-term suspension of statins is safe for at least patients with stable cardiovascular disease [9]. Complications related to this short-term suspension of lipid-lowering therapy have not been observed so far in our institute.…”
Section: Study Subjectsmentioning
confidence: 61%